36.3k views
0 votes
Solve the simultaneous equations
2x + 3y = 6
7x – 2y = 1

User Brosig
by
5.0k points

2 Answers

5 votes

Answer:

x=0.6, y=1.6

Explanation:

Multiply the first equation by 2 and the second equation by 3, so we can cancel out the y terms:

4x+6y=12

21x-6y=3

Add these 2 equations together:

25x=15

x=0.6

Now, to solve for y, plug x back into any of the equations above:

2(0.6)+3y=6

1.2+3y=6

3y=4.8

y=1.6

User Nikita Sivukhin
by
4.9k points
7 votes

Answer:

Below in bold.

Explanation:

2x + 3y = 6 Multiply by 2:

7x – 2y = 1 Multiply by 3:

4x + 6y = 12

21x - 6y = 3 Adding:

25x = 15

x = 0.6. Substitute x = 0.6 into the first equation:

2*0.6 + 3y = 6

3y = 6 - 1.2 = 4.8

y = 1.6.

User Maharshi
by
5.0k points